Correlated evolution of diaspore traits and potential frugivore‐mediated selection in a fleshy‐fruited tropical lineage (Artabotrys, Annonaceae). (6th July 2020) - Chen, Junhao; Thomas, Daniel C.; Saunders, Richard M. K.
Abstract: Dispersal syndromes are often defined by reference to fruit traits that are associated with distinct frugivore guilds. Studies rarely examine the relationship between seed traits and frugivores or test the alternative hypothesis that traits are shaped by climatic variables. We assess whether the evolution of seed size and physical defense are correlated with dispersal‐related traits and climatic variables in Artabotrys, a fleshy‐fruited tropical lineage. Diaspore traits and WorldClim bioclimatic variables were compiled for 43 species. Correlated evolution was evaluated using phylogenetic regression and model‐fitting approaches. The best‐fitting multioptima Ornstein‐Uhlenbeck model suggests that lineages with smooth testa and thin pericarp (SP) have evolved toward smaller seeds with a thinner testa, whereas lineages with rough testa and/or thick pericarp have evolved toward larger seeds with a thicker testa. A smooth testa facilitates spitting and/or swallowing of intact seeds while fruits with thin pericarp may be preferentially consumed by frugivores with less destructive oral processing, enabling lower investment in seed physical defense in SP lineages. Moreover, small seeds are more likely to be swallowed intact with a food bolus. The effect of climate on seed size and physical defense is equivocal and warrants further investigation.